How can a local company face the competition of a multinational company? Industrias Ramo vs. Bimbo de Colombia - Lombana Roa, Juan José; León Guatame, Aida Ximena (Estudios de Administración, 2020)
Productos Ramo S.A.S. (a simplified joint-stock company), leader in the pastry and bakery sector in Colombia since 1956, especially in the city of Bogotá, had been competing in a relatively stable environment for many years, with no major competitors until 1995, when the Mexican multinational Bimbo entered the market (as Bimbo de Colombia S.A.). This company initiated its operations by generating a differentiation in the market, positioning itself as premium brand in the bread products line. It also launched a broad portfolio of products and thanks to an efficient distribution process managed to permanently alter the market, achieving accelerated growth and assuming its leadership. In the year 2006, Bimbo de Colombia recorded 7% more sales and revenue than Productos Ramo, and by 2018, this difference in revenue had grown to 45% (while Productos Ramo sold USD 247 million, Bimbo sold USD 360 million in Colombia). Faced with this situation, the General Manager of Productos Ramo wondered: What strategy could he implement to confront Bimbo and regain his leadership in the Colombian market? The case study is divided into four parts, as follows: firstly, there is a presentation of the history of Productos Ramo S.A.S.; secondly, it addresses the entry of Bimbo into the Colombian market; the third part presents the response or reactions of Productos Ramo to the entry of this new competitor and finally, strategic concerns are raised about the future for Productos Ramo.